Influence of industrial relations with ukhuwwah (brotherhood), ‘adl (justice) and ihsan (benevolence) among Islamic universities - Mhd. Sarif, Suhaimi; Syed Ahmad, Sharifah Fazirah; Zainudin, Dolhadi; Ismail, Yusof; Firmansah, Yayan (AMH International, 2024)
The existence of industrial relations with the industrialization drivers has been argued with the persistent competition among different entities, including workers, capitalists, bureaucrats, and authorities, to reduce operating costs while maximizing financial profits. While industrial relations have been relevant through the human resource management of organizations, from the perspectives of Islam, three core values, ukhuwwah (brotherhood), ‘adl (justice), and Ihsan (benevolence) are essential in establishing a harmonious and ethical relationship between employers and employees, which serves as a solid foundation for creating a positive work environment. This study used the grounded theory method through focused group discussion to explore the integration of Islamic values into the industrial relations of Islamic universities. It focuses on insights from participants who emphasized the significance of promoting positive human relationships, incorporating Islamic teachings, and maintaining a balance between procedural work and community-building activities. The study suggests incorporating these principles can establish a cohesive and morally upright work environment that benefits employees and organizations. Suggestions for the industrial relations unit, top management, board of governors, and the government involve cultivating strong unity through team-building, maintaining fairness with clear and open policies, and promoting excellence by supporting professional growth and empathetic work conditions.